Long noncoding RNA H19 mediated the chemosensitivity of breast cancer cells via Wnt pathway and EMT process - Gao, Hongli; Hao, Guijun; Sun, Yue; Li, Liye; Wang, Yukun (OncoTargets and therapy, 2018)
Breast cancer is still one of the major public health burdens worldwide, although there is tremendous progress in early diagnosis and treatment of breast cancer. Tamoxifen was one of the most popular endocrine therapies for early-stage estrogen receptor (ER) + breast cancer patients. However, a high incidence of drug resistance develops along with poor prognosis in breast cancer. Currently, long noncoding RNAs (lncRNAs) are emerging and are well suited to play a role in the development of cancer and tamoxifen resistance. However, there is little reported about the relationship of breast cancer resistance to tamoxifen and lncRNA H19. Here, we validated that lncRNA H19 was highly expressed in breast cancer especially in patients with late stage (III and IV), compared to normal tissues and early stage cancers (I and II). Quantitative polymerase chain reaction (qPCR) was utilized for comparison of lncRNA H19 expression level in breast cancers with different stages. qPCR and Western blotting were used to detect gene and protein, respectively. We found that lncRNA H19 expression level manipulated breast cancer cell proliferation both in parental breast cancer cell lines and tamoxifen-resistant cell lines. Knockdown of lncRNA H19 elevated tamoxifen sensitivity for promoting cell growth and inhibiting apoptosis in tamoxifen-resistant breast cancer cells. Moreover, knockdown of H19 inhibited Wnt pathway and epithelia-mesenchymal transition in tamoxifen-resistance breast cancer cells. Taken together, the results of this study provided the evidence for H19 in regulating tamoxifen-resistant breast cancer and might provide novel options in the future treatment of tamoxifen-resistance breast cancer patients.